Evaluation of Use of Web-Based PolAc-D Application - Silfia Dewi; Fithriany Fithriany; Cut Nurhasanah; Lili Kartika Sari Harahap (Postgraduate, University of Mataram, 2023)
Maternal and child health is a national policy that is one of the strategic plans, namely the challenge of making pregnancy safer. One of the main strategies implemented is to increase access and reach of quality maternal and neonatal health services to reduce maternal and infant mortality. PolAc-D is a web-based application that has been designed to monitor the health of pregnant women and fetuses. The purpose of this study was to evaluate the use of the PolAc-D application. The research method is a survey with a questionnaire that has been tested for validity and reliability, the sample used is all midwives who are in the Work Area of ​​the Langsa Baro Health Center, totaling 47 people. The results obtained a total score of 2,136, an average value of 45.4, for a maximum score of 53 and a minimum score of 39. These results mean that the evaluation of the use of the polAc-D application is very good, both in terms of use, application features that are easy to understand and according to the services that are carried out by midwives every day in providing services.